2008
DOI: 10.1007/s00392-007-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined cardiac surgical procedures in octogenarians: operative outcome

Abstract: Octogenarians requiring combined cardiac surgical procedures required more resources and had a higher in-hospital mortality compared to younger patients. The observed in-hospital mortality was much lower than the predicted justifying the indication for surgical therapy in these patients. Patient selection, however, seems to be important but the Euro-score alone was rather ineffective in predicting poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…13,29,30 Our series is consistent with these reports, with 6-year survival of 54.7% in 16 in their series of 196 octogenarians found that simultaneous CABG had no effect on 60-day mortality (relative risk, 0.96; 95% CI, 0.54 to 1.70) and a statistically insignificant increased median late survival: 7.4 years (95% CI, 6.4 to 13.3) for patients after AVRϩCABG versus 6 years (95% CI, 5.4 to 8.9) for patients after AVR. Our present findings are similar to those of Gulbins et al, 31 who showed that in-hospital mortality rates were higher among patients having AVRϩCABG versus those undergoing AVR (10% versus 4%, PϽ0.05). Gulbins et al 31 suggested that the additional risk of mortality was acceptable, given a lower observed mortality rate relative to that predicted through the use of Euroscore.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…13,29,30 Our series is consistent with these reports, with 6-year survival of 54.7% in 16 in their series of 196 octogenarians found that simultaneous CABG had no effect on 60-day mortality (relative risk, 0.96; 95% CI, 0.54 to 1.70) and a statistically insignificant increased median late survival: 7.4 years (95% CI, 6.4 to 13.3) for patients after AVRϩCABG versus 6 years (95% CI, 5.4 to 8.9) for patients after AVR. Our present findings are similar to those of Gulbins et al, 31 who showed that in-hospital mortality rates were higher among patients having AVRϩCABG versus those undergoing AVR (10% versus 4%, PϽ0.05). Gulbins et al 31 suggested that the additional risk of mortality was acceptable, given a lower observed mortality rate relative to that predicted through the use of Euroscore.…”
Section: Discussionsupporting
confidence: 92%
“…Our present findings are similar to those of Gulbins et al, 31 who showed that in-hospital mortality rates were higher among patients having AVRϩCABG versus those undergoing AVR (10% versus 4%, PϽ0.05). Gulbins et al 31 suggested that the additional risk of mortality was acceptable, given a lower observed mortality rate relative to that predicted through the use of Euroscore.…”
Section: Discussionsupporting
confidence: 92%
“…Table 4 presents the in-hospital mortality rates of high-risk patients undergoing SAVR. The 30-day mortality rate of 9.6% observed in TAVI patients in our study is encouraging in light of the reported inhospital mortality rates of selected octogenarians (4.6% to 13.5%) [4][5][6][7][8][9][10][11] , patients with left ventricular dysfunction (6% to 33%) 12,13,[26][27][28][29][30][31] and patients with high logistic EuroSCORES (7.8%) undergoing surgical aortic valve replacement 32 . While surgical heart valve replacement remains the standard of care, several studies have demonstrated that 30% to 60% of patients with symptomatic severe aortic valve stenosis are denied or not referred for surgery [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 62%
“…Contemporary studies indicate that the 30-day mortality rate following TAVI is 8% to 12% [1][2][3] . Following SAVR, the 30-day mortality rate in high-risk patient subsets was reported to be between 4.6% to 13.5% for octogenarians [4][5][6][7][8][9][10][11] and 6% to 33% for patients with left ventricular dysfunction 12,13 . To our knowledge, direct comparisons between TAVI and SAVR are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Gulbins et al [18 ]also observed higher mortality rates in patients undergoing AVR/CABG compared to those undergoing either AVR or CABG alone, concluding that the additional risk of mortality was real, but actually lower than that predicted, based on the EuroSCORE. Although combined AVR and CABG does carry with it a significantly higher mortality risk in the immediate postoperative period, this appears primarily related to the increased complexity of the procedure rather than something intrinsic to the patient selection process, as similar preoperative comorbidities and postoperative complications have been present in patients undergoing AVR alone, CABG alone or combined procedures (table 7) [9,17].…”
Section: Discussionmentioning
confidence: 99%